Sistemas químicos auto-organizados: morfogênese e formação de padrões - Silva-Dias, Leonardo (2024)
Chemical systems maintained far from equilibrium, with spatially extended reaction domains, and composed of chemicals that interact non-linearly with each other, can spontaneously evolve to organized states of low entropy, known as dissipative structures. These structures are commonly observed in living organisms, and the most notable are: periodic oscillations of chemical concentration, chemical chaos, chemical waves, and stationary patterns (Turing patterns). This class of self-organized chemical systems comprises a significant number of inorganic chemical reactions with well-known mechanisms. Due to this fact, along with the dynamical similarities of these reactions to living organisms' dynamics, and the complexity of reaction mechanisms in chemical-biological processes, inorganic chemical systems are often considered in studies of dynamical phenomena in different scenarios in order to obtain results that can be extrapolated to understanding similar phenomena in living systems. From this perspective, this thesis presents an investigation of morphogenesis and spatio-temporal pattern formation in conditions that are either relevant or motivated by biology. This is accomplished through four main works. In the first, we investigated the emergence of Turing patterns in the chlorine dioxide–iodine–malonic acid (CDIMA) reaction in a domain that continuously grows as a rotating spiral. From this study, we observed the formation of a new class of stationary spiral patterns with different multiplicities. In the second, we evaluated the effects of Faraday waves on the formation of chemical waves in the Belousov-Zhabotinsky reaction, aiming to discriminate acoustic frequencies through the spatio-temporal dynamics of the reaction. We noted that Faraday waves interfere with the local process of mixing, altering the speed and morphology of the chemical waves. However, this system was ineffective in discriminating the applied acoustic frequencies. In the third work, we developed a simple and practical procedure to obtain transient Turing patterns in a batch system from the CDIMA reaction. From such an experimental procedure, we obtained patterns with good resolution and stability. Finally, in the fourth one, we proposed a model based on the classical theory of phase separation and reaction-diffusion systems to describe morphogenesis in a system of synthetic chemical cells. Through numerical simulations, we were able to elucidate the physical-chemical mechanism of this process and to identify that the difference in osmotic pressure between two cells in different chemical states, due to the break of spatial symmetry caused by the emergence of a Turing state, triggers the physical morphogenesis.